The Good, the Bad, and the Ugly: What the Future Could Hold for Bs2 Tomatoes - Samuel F. Hutton; John W. Scott; Jeffrey B. Jones; Robert E. Stall; Gary E. Vallad; B. J. Staskawicz; D. M. Horvath (EDIS, 2015)
Bs2 tomatoes are transgenic tomatoes that have been engineered to contain the Bs2 gene from pepper. As such, they are considered a genetically modified (GM) food, or a genetically modified organism (GMO). Numerous trials conducted by University of Florida researchers have shown the benefits of these cultivars for bacterial spot disease management, and growers and industry members recognize the potential for Bs2 tomatoes to make Florida tomato production more sustainable. This 4-page fact sheet discusses the benefits that might be realized by the adoption of Bs2 tomato varieties, and the challenges standing in the way of their commercial production. Written by S. F. Hutton, J. W. Scott, J. B. Jones, R. E. Stall, G. E. Vallad, B. J. Staskawicz, and D. M. Horvath , and published by the UF Department of Horticultural Sciences, April 2015.